Adobe Premiere Pro CS3 - Gonzalez, James; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
Learn how to edit clips and sequences, add titles, effects and transitions, work with audio tracks, and export your results to a variety formats including CD-ROM, video tape, web and more
Title from container
Trainig CD
Contains 98 movies with total time 8 hours
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Adobe Premiere; Motion pictures -- Editing -- Data processing; Multimedia systems